BRAND AWARENESS, BRAND LOYALTY, BRAND ASSOCIATION, DAN PERCEIVED QUALITY TERHADAP CUSTOMER LOYALTY LAYANAN MOBILE BANKING M-BCA - Sintara Kunfahmi Padmawati; Ari Susanti (JURNAL LENTERA BISNIS, 2023)
Digitalization in the banking industry has had an impact on the pressure to keep abreast of the times by making various adjustments that have triggered many banks to compete to provide innovative online banking services and increase their existence to maintain customer loyalty. This research aims to determine the effect of brand awareness, brand loyalty, brand association and perceived quality on customer loyalty. The type of research carried out is quantitative research. The population in this research is M-BCA service customers in Solo Raya who have the M-BCA mobile banking application and have used M-BCA mobile banking at least 5 times. The sample used was 100 respondents who were taken using the purposive sampling technique and the data collection method used in this study was a questionnaire. The results of the analysis using multiple linear regression explained that the brand awareness variable did not have a significant effect on the customer loyalty variable, while the brand loyalty, brand association and perceived quality variables had a significant effect on customer loyalty. The results of the F test analysis explain that brand awareness, brand loyalty, brand association and perceived quality simultaneously have a significant influence on customer loyalty.Key words: Brand Awareness, Brand Loyalty, Brand Association, Perceived Quality, Customer Loyalty.